Measurements of Higgs boson production cross-sections in the H ? ? + ? ? decay channel in pp collisions at ?s = 13 TeV with the ATLAS detector - Çetin, Serkant Ali (Springer Science and Business Media Deutschland GmbH, 2022)
Abstract: Measurements of the production cross-sections of the Standard Model (SM) Higgs boson (H) decaying into a pair of ?-leptons are presented. The measurements use data collected with the ATLAS detector from pp collisions produced at the Large Hadron Collider at a centre-of-mass energy of s = 13 TeV, corresponding to an integrated luminosity of 139 fb?1. Leptonic (? ? ?????) and hadronic (? ? hadrons ??) decays of the ?-lepton are considered. All measurements account for the branching ratio of H ? ?? and are performed with a requirement |yH| < 2.5, where yH is the true Higgs boson rapidity. The cross-section of the pp ? H ? ?? process is measured to be 2.94 ±0.21(stat)?0.32+0.37(syst) pb, in agreement with the SM prediction of 3.17 ± 0.09 pb. Inclusive cross-sections are determined separately for the four dominant production modes: 2.65 ±0.41(stat)?0.67+0.91(syst) pb for gluon-gluon fusion, 0.197 ±0.028(stat)?0.026+0.032(syst) pb for vector-boson fusion, 0.115 ±0.058(stat)?0.040+0.042(syst) pb for vector-boson associated production, and 0.033 ±0.031(stat)?0.017+0.022(syst) pb for top-quark pair associated production. Measurements in exclusive regions of the phase space, using the simplified template cross-section framework, are also performed. All results are in agreement with the SM predictions. [Figure not available: see fulltext.] © 2022, The Author(s).
Keywords: Hadron-Hadron Scattering; Higgs Physics; Tau Physics